Rättskraft i skiljeförfarandet – särskilt om parternas möjligheter att disponera över skiljedomens negativa rättskraft - Andersson Telander,Linnea (2024)
Arbitration is classified as a judicial dispute resolution method in Sweden, and its awards are enforceable under Chapter 3, Section 15 of the Enforcement Code. Despite these provisions, the Swedish Arbitration Act does not contain any provision stating that an arbitral award is endowed with legal force. However, The Supreme Court has clarified through its rulings in NJA 1953 p. 751 and NJA 1998 p. 189 that arbitral awards do acquire legal force. Primarily, it is the principles of legal force in civil procedure that should guide the assessment of the scope of legal force in arbitration. However, there is disagreement in the legal literature regarding the precise boundaries of an arbitral award's legal force and whether there are unresolved differences between civil procedure and arbitration as dispute resolution methods that justify deviating from the civil procedural res legal force framework. The aim of this thesis is to examine the extent of legal force in arbitration. Given that party autonomy is fundamental in arbitration, the parties' own ability to influence the scope of the legal force is a natural part of the investigation. Since the civil procedural principles’ for determining the extent of legal force are central also to arbitration, these are addressed as well as the parties' ability to influence the legal force of a court judgment. Since arbitral awards are not public, there is a limited body of practical examples regarding how the legal force issue is handled. Therefore, the study will focus on the respective characteristics of different dispute resolution methods and what their implications may and should be, from a principled perspective, for legal force. In conclusion, I will argue that the legal force effect of an arbitral award should be determined according to the precedential rules developed for this purpose in civil procedure. The Arbitration Act should not be systematically interpret-ed in the same way as the Code of Judicial Procedure, where there is a close connection between the rule on changing claims and the rule on res judicata. Furthermore, in arbitration, there is a possibility for the parties, after an arbitral award has been issued, to agree that it will no longer be procedurally bind-ing. It is also possible to agree in advance that an arbitral award will not be endowed with legal force. It is more uncertain whether the parties can extend the effect of legal force with binding effect, either through a separate agreement or by confirming a settlement with far-reaching supplementary elements. Certain case law suggests such an interpretation. Despite the autonomy of the parties in arbitration, my view is that this does not have an impact on the question of the possibility to extend the res judicata effect. This issue should ultimately be considered in light of Article 6.1 of the European Convention on Human Rights (ECHR) and the right to a judicial review therein. An overly extensive preclusion could risk preventing the parties from asserting their civil rights.
Keywords: civilrätt; processrätt